The Changing Role of Strategy and Design: Evidence-Based Investigation toward an Interdisciplinary Approach - Cem Bora Okandan; Deniz Elber Börü (Istanbul Management Journal)
Contemporary developments have triggered the emergence of interdisciplinarity, which fosters learning across different areas of expertise. Particularly, the volatility, uncertainty, complexity and ambiguity (VUCA) are reshaping perspectives across all management-related areas, from private to public sectors and from strategy to policy level. This article explores the historical developments of strategy and design and how these domains are converging toward an interdisciplinary perspective: design management or strategic design. Over the last 40 years, developments in each domain have posed common questions and established the interdisciplinary intersection of design management, relying on the notion of design culture and proposing alternatives to achieve sustainable competitive advantage. These discussions have extended beyond academia to boardrooms, fostering innovative solutions and becoming focal points for management consulting firms. This article examines how this intersection and interdisciplinarity are shaping management consulting services and empowering firms that act as early adopters of collective, participatory, iterative, and evidence-based design-oriented methodologies.